Effects of maternal BMI on early pregnancy endocrine–metabolic function and offspring development: Evidence from a retrospective cohort and animal model - Wendi Shen; Ana Niu; Qiying Zhang; Jialing Deng; Xinya Xu; Xian Ma; Hongli Zhao; Yiyun Lou (PLoS ONE, 2026)
Objective Abnormal body mass index (BMI) has been associated with pregnancy complications and adverse pregnancy outcomes; however, its clinical significance during early pregnancy remains unclear. This study aimed to investigate the relationships and underlying mechanisms between maternal BMI, reproductive endocrine parameters, and pregnancy outcomes, thereby providing a theoretical basis and clinical guidance for the management of pregnancies in women with abnormal BMI. Methods A total of 353 pregnant women were enrolled in this study and categorized into four groups according to BMI: underweight (n = 45), normal weight (n = 229), overweight (n = 57), and obese (n = 22). At 6–8 weeks of gestation, pregnancy-related hormones, glucose and lipid metabolism parameters, and uterine artery blood flow indices were collected and analyzed. Pregnancy outcomes and neonatal birth information were also recorded. In addition, an obese mouse model was established to evaluate maternal weight changes during pregnancy and their effects on uterine and embryonic development. The expression of genes and proteins related to en[docrine metabolism, inflammatory regulation, and angiogenesis was assessed using RT-qPCR and Western blot techniques to further explore the potential mechanisms involved. Results During early pregnancy, pregnant women with low BMI exhibited significantly lower estradiol levels ( P < 0.05). In contrast, women with high BMI had significantly reduced levels of human chorionic gonadotropin, estradiol, and progesterone, along with markedly elevated glucose and lipid metabolism parameters ( P < 0.05). However, BMI had no significant impact on uterine artery blood flow indices, live birth rate, gestational age, or mode of delivery ( P > 0.05). High BMI was associated with an increased risk of macrosomia in neonates ( P < 0.05). In the animal experiments, obese pregnant mice exhibited significantly greater gestational weight gain compared to controls ( P < 0.05), and their offspring showed a predisposition to obesity. RT-qPCR analysis revealed that, relative to the control group, mRNA expression levels of VEGFA, VEGFR-2, CD31, and SIRT1 were significantly decreased in the obese group ( P < 0.001), whereas mRNA expression of GLUT1, HIF-1α, TNF-α, IL-6, HMGB1, and TLR4 was significantly upregulated ( P < 0.01). Western blot results demonstrated that compared with controls, the obese group showed significantly lower expression levels of GLUT4 and phosphorylated IRS1 ( P < 0.0001), while the expression of HIF-1α and TNF-α was significantly increased ( P < 0.0001). Additionally, there were no significant differences in the protein expression levels of IRS1, SGK1, and NFκB p65 between the two groups ( P > 0.05). Conclusion Abnormal BMI affects hormonal profiles and glucose and lipid metabolism during early pregnancy. Although it does not significantly impact fetal survival rates, it markedly increases the risks of cesarean delivery, preterm birth, and abnormal neonatal birth weight. These alterations not only pose challenges for postpartum maternal and neonatal health management but may also exert adverse effects on the long-term health of the offspring. Maternal obesity may impair pregnancy outcomes by inhibiting insulin signaling, enhancing proinflammatory responses, inducing a hypoxic microenvironment in the decidual tissue, and suppressing angiogenesis, thereby disrupting maternal–fetal interface homeostasis.